The Instigatory Theory of NGO Communication Strategic Communication in Civil Society Organizations - Oliveira, Evandro; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
By understanding the ontogenesis of NGOs as civil society organizations from a historical-anthropological, communicational, sociological, economical and managerial perspective, Evandro Oliveira outlines the Instigatory Theory of NGO Communication (ITNC). This proposes the ontological principles, an applied conceptual model and a cybernetic operational model for understanding and managing communication at NGOs. Those models were tested using a mixed-method research design. The content • Strategic communication and NGOs • Logics and management • NGOs and social theory: social and economic dimensions • Fundraising • Volunteering • Civic relations and social change The target groups • Students and lecturers in the field of public relations, sociology, economics, management and communication • Practitioners in NPOs, NGOs and civil society organizations The author Prof. Dr. phil., rer. pol Evandro Oliveira is Professor for corporate communication at the University of Applied Sciences in Berlin (HMKW). He is also lecturing at the Free University of Berlin and University of Mannheim, among others. He is the vice-chair of the section Organizational and Strategic Communication of the international academic PR association ECREA. His main research interests are strategic communication, NGO and civil society organizations communication management, social media and political communication.
Strategic communication and NGOs -- Logics and management -- NGOs and social theory: social and economic dimensions -- Fundraising -- Volunteering -- Civic relations and social change.
Keywords: Communication; Communication in organizations; International organization; Media and Communication; Corporate Communication; International Organization